THE EFFORTS TO IMPROVE STUDENTS' LEARNING OUTCOMES TOWARDS HISTORICAL EVENTS IN SOCIAL SCIENCE LEARNING THROUGH THE ROLE-PLAYING MODEL IN 5TH GRADE SD NEGERI KADUDAMPIT 1 - Nurhasanah Nurhasanah; Hadariah Hadariah (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThis research is motivated by the existence of learning that is still dominated by teacher activities (teacher-centered), where the teacher acts as a transmitter of information and students are not much involved in the learning activities. This illustration shows that the learning obtained by students is less meaningful. As an implementation, Classroom Action Research (CAR) was conducted by applying the discussion method to increase the student’s interest, activity, and learning outcomes in social science learning in elementary schools. This research uses a series of steps from planning, action, observation, and reflection which consists of 2 cycles. The data collection techniques were conducted using research instruments, namely observation guidelines, field notes, interview sheets, evaluation sheets, and student worksheets. The use of the discussion method allows the learning to be student-centered and the teacher only guides and directs. The conclusion of this research is the discussion method in social science learning, especially the material of people’s resistance during the Dutch and Japanese colonial times, has been able to increase activity, where the students have actively cooperate, express opinions, and provide responses to their friends’ opinions. This can be seen from the average score acquisition of the individual evaluation of each cycle. The average pre-cycle score is 54.62, the average student score in cycle I is 67.69, and the average student score in cycle II is 86.92. The average score shows that the mastery level of the material that has been delivered is above 96.15%.Keyword: Students’ Learning Outcomes; Role Playing